IMPROVING THE ECONOMY OF ARECA NUT FARMERS IN SIMPANG JERNIH VILLAGE THROUGH INCREASING VALUE ADDED WITH POST-HARVEST PROCESSING OF ARECA NUTS - Faoeza Hafiz Saragih; Haikal Fajri; Andri Yusman Persada (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
Areca nut is a commodity with high economic value, where Areca nut is used in industry as a food and textile colouring. However, many farmers do not cultivate Areca nuts specifically; they only plant them as a plant on the fence of the house or agricultural land. In Simpang Jernih Village, areca nut is still processed traditionally so that it gets an inappropriate selling value. The post-harvest process is not productive and the sale of areca nut is still round. Therefore, a tool technology is needed that can be used to increase productivity, such as peeling areca nuts and cutting areca nuts into slices so that they can increase the selling price. This community service activity will be carried out in Simpang Jernih Village, Simpang Jernih District, East Aceh. The result of this workshop that the areca nut farmer more efficiently in post-harvest and the price of slice areca nut more expensive then before.